Near-IR diode laser-based sensor for remote sensing of methane leakage - Wei, Huang; Xiaoming, Gao; Xiaoyun, Li; Weizheng, Li; Teng, Huang; Shixin, Pei; Jie, Shao (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
A tunable diode laser-based sensor for remote sensing of methane (CH4) leakage at a wavelength of 1.65 mm was developed. The 1.65 mm distributed feedback (DFB) diode laser has a narrow line width and a wide tuning range. It was found that the sensor can detect a 10 cm3min–1 city-gas leak with a sensor output equivalent to the range-integrated concentration over 100 ppm·m.
Optica Applicata, Vol. 35, 2005, nr 1, s. 23-32
Keywords: optyka; wavelength modulation spectroscopy; tunable diode laser spectroscopy; methane; gas sensor; diode laser